Eemporary Measures Regarding Spouses During Divorce Proceedings Pursuant to Turkish Civil Code Article 169 - Efe Can Yıldırır (İstanbul Hukuk Mecmuası)
Pursuant to Article 169 of the TCC, temporary measures offer legal protection and prevent the conflict between parties during proceedings from the filing of a divorce case until finalization of the decision. Despite the divorce case being filed, rights and obligations continue to arise from the marital union, which continues to exist during the judgment process. This study examines these temporary legal protections specific to family law, which provides a temporary order between spouses and simultaneously functions to help spouses reestablish a common life in case the proceedings do not end with divorce. Thus, the right of the spouses to live separately; allocation of the use of the family dwelling; injunctive alimony and measures related to the property relations of the spouses, especially transition to the extraordinary property regime; restrictions on power of disposal; and ordering debtors to pay one of the spouses are analyzed according to Turkish and Swiss doctrine and practice. Notably, the measures are primarily analyzed in terms of substantive law. To reflect the practice appropriately after the examination of the content, determinations have been made in terms of procedural law, especially in light of decisions of the Court of Cassation and by comparison at times with measures of protection of marital union. Measures regulated under Law No. 6284 on the Protection of the Family and Prevention of Violence against Women are excluded from the scope.